Cranial ultrasound in high-risk neonates and their neurodevelopmental outcome - Dr. Ruby Singh; Dr. Chandan Shaw; Dr. Shachi Jain Taran; Dr. Veerendra Mehar; Dr. Aman Gupta (Pediatric Review: International Journal of Pediatric Research, 2020)
Introduction: With the advancement in neonatal care over the last two decades, neonatal mortality is decreased but simultaneously there is an increase in the adverse outcomes including neurodevelopmental abnormalities in the high-risk neonates. Purpose: To evaluate the association between cranial ultrasound findings and the clinical neurodevelopmental outcome among high-risk neonates at 12 months (corrected gestational age in preterm infants) and to assess the various perinatal risk factors associated with neurodevelopmental outcome. Material and Methods: 123 high-risk neonates admitted in NICU were enrolled. Cranial ultrasound was performed and morphology was noted. The neurodevelopmental assessment was done using DDST Test II at 12 months age and these neonates were labeled as normal or abnormal based on the findings. Association between the two non-parametric variables was seen using the Pearson Chi-square test. Results: There was a statistically significant association between clinical neurodevelopmental outcome and gestational age at birth; birth weight; Apgar score <5 at 5 minutes; neonatal seizures; and abnormal cranial ultrasound findings (p<0.05), while the association with all other studied parameters were found to be statistically not significant (p>0.05). The sensitivity of CUS was 89.2%, specificity 47.3%, positive predictive value 89.2%, and negative predictive value 47.3%. Conclusions: The neurodevelopmental outcome in high-risk neonates was associated with gestational age at birth; birth weight; Apgar score at 5 minutes; neonatal seizures and abnormal cranial ultrasound findings. The current study recommend the use of cranial ultrasound for the prediction of neurodevelopmental abnormalities especially in neonates with above risk factors.